Influences from and influences on Europe: the evolution of spatial planning and territorial governance in Finland. - Fritsch, Matti; Eskelinen, Heikki (TH Zürich, NSL, 2011)
Die Gleichzeitigkeit der beschleunigten wirtschaftlichen und sozialen Transformation, der geopolitischen Neuausrichtung und der zügigen Integration in die Europäische Union macht Finnland zu einem interessanten Untersuchungsfeld der Prozesse der Europäisierung territorialer Governance und Raumplanung. Der Beitrag untersucht die Art und Weise, auf die "Europa" in seinen verschiedenen Ausprägungen Finnlands territoriale Governance beeinflusst und mitgeformt hat. Der Schwerpunkt liegt dabei auf den institutionellen Voraussetzungen und den ihnen zugrundeliegenden Entscheidungen. Die Ergebnisse können keinen signifikanten Prozess der Konvergenz der räumlichen Planung in Finnland belegen.

Simultaneous processes of accelerated socio-economic transformation, geopolitical repositioning and rapid integration into the EU make Finland an interesting case and testbed for the analysis of processes of Europeanization of territorial governance and spatial planning. Focusing on institutional preconditions and underlying debates, this paper explores the ways in which "Europe" (in its manifold forms) has shaped and influenced Finnish territorial governance and how Finland has attempted to upload domestic interests to the European agenda. EU regional governance requirements, the spread of European planning concepts, and a Nordic epistemic community are identified as important catalysts for Europeanization. Overall, the findings cannot be taken as an indication of significant process of convergence of spatial planning and territorial governance in a European context. Instead, they represent a case of a country's specific engagement with the EU dimension in territorial governance.
Keywords: Raumplanung; Planungssystem; Planungsorganisation; Raumplanungsbehörde; Raumplanungsinstitution; Planungspraxis; Planungsinstrument; Planungspraxis; Raumplanungspolitik; Europäisierung; Planungskultur; Raumplanungshoheit; Raumplanungsprogramm; Akteur; Konvergenz; Territoriale Governance; Governance; Planungsgeschichte; Raumentwicklungspolitik; Institutionenforschung; Politikforschung